Mechanistic Divergence in the Hydrogenative Synthesis of Furans and Butenolides: Ruthenium Carbenes Formed by gem‐Hydrogenation or through Carbophilic Activation of Alkynes. (6th November 2019) - Peil, Sebastian; Fürstner, Alois
Abstract: Enynes with a tethered carbonyl substituent are converted into substituted furan derivatives upon hydrogenation using [Cp*RuCl]4 as the catalyst. Paradoxically, this transformation can occur along two distinct pathways, each of which proceeds via discrete pianostool ruthenium carbenes. In the first case, hydrogenation and carbene formation are synchronized ("gem‐hydrogenation"), whereas the second pathway comprises carbene formation by carbophilic activation of the triple bond, followed by hydrogenative catalyst recycling. Representative carbene intermediates of either route were characterized by X‐ray crystallography; the structural data prove that the attack of the carbonyl group on the electrophilic carbene center follows a Bürgi–Dunitz trajectory. Abstract : Auf die eine oder andere Weise : Enine mit einer angebundenen Carbonylgruppe wurden durch katalytische Hydrierung mit einem Rutheniumkatalysator in Furane umgewandelt. Die Reaktion folgt zwei individuellen Pfaden, wovon jeder ein diskretes Metallcarben‐Intermediat involviert. Sie unterscheiden sich darin, dass Hydrierung und Carbenbildung entweder synchron ( gem ‐Hydrierung) oder gänzlich voneinander entkoppelt erfolgen.